ANALISA FAKTOR YANG DIANGGAP BAIK OLEH MASYARAKAT DI SURABAYA DALAM MENGAKSES SITUS HOTELv - Jesslyn Nathania; Patricia Sampurno; Hanjaya Siaputra (Jurnal Hospitality dan Manajemen Jasa, 2017)
Situs hotel adalah kumpulan halaman web yang saling terhubung, yang dimiliki oleh sebuah akomodasi bertujuan komersial. Penelitian ini melihat kriteria situs hotel berbintang tiga hingga lima yang baik menurut masyarakat Surabaya, menggunakan metode analisis faktor eksploratori. Penelitian ini dilakukan pada seratus sampel masyarakat Surabaya yang pernah mengakses situs hotel bertujuan untuk menemukan faktor situs hotel yang baik. Setelah pengolahan data, peneliti telah menemukan sepuluh faktor baru yang terbentuk, yaitu reservation, accessibility, tourist attraction information, hotel’s other features, hotel’s brand and customer’s account, job vacancy and ease of use, approach convenience, local information, website extra facilities, dan meeting facilities and special request forms. Hotel’s website is a bunch of webpage that are connected that is owned by a lodging accommodation for commercial purpose. This study is going to observe Surabaya’s society perception on accessing three star to five star hotel’s website and exploratory factor analysis method is used. This study using a hundred samples as respondents from Surabaya’s society that have been accessing hotel’s website aim to create good hotel website. After data collection, researchers found ten new factors, reservation, accessibility, tourist attraction information, hotel’s other features, hotel’s brand and customer’s account, job vacancy and ease of use, approach convenience, local information, website extra facilities, and meeting facilities & special request forms.